Вплив гелю «Лізостом» на судинно-тромбоцитарний гемостаз = Influtnce of gels «Lizostom» on the vascular-platelet hemostasis - N. S. Kavushevska; A. I. Bereznyakova; O. D. Zhemela (Kazimierz Wielki University, 2016)
Kavushevska N. S., Bereznyakova A. I., Zhemela O.D. Вплив гелю «Лізостом» на судинно-тромбоцитарний гемостаз = Influtnce of gels «Lizostom» on the vascular-platelet hemostasis Journal of Education, Health and Sport. 2016;6(10):415-422. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.163976 http://ojs.ukw.edu.pl/index.php/johs/article/view/3967     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7                                                                                                                                      © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 30.10.2016.   УДК 616. 31002:616. 311. 2002:616. 314. 17008. 1:61608   ВПЛИВ ГЕЛЮ «ЛІЗОСТОМ» НА СУДИННО-ТРОМБОЦИТАРНИЙ ГЕМОСТАЗ   Н. С. Кавушевська*, А. І. Березнякова*, О. Д. Жемела**   *Національний фармацевтичний університет, м. Харків ** Харьківський національний університет ім. В. Н. Каразіна   Резюме В ході експериментальних досліджень було доведено вплив стоматологічного гелю «Лізостом» на зменшення тривалості кровотеч з мікросудин, підвищення кількості тромбоцитів та їх агрегаційної здатності; зростання показника ретракції згустку крові. Ключові слова: гель «Лізостом», судинно-тромбоцитарний гемостаз,  лізоциму гідрохлорид.    INFLUENCE OF GELS «LIZOSTOM» ON THE VASCULAR-PLATELET HEMOSTASIS     N. S. Kavushevska*, A. I. Bereznyakova*, O. D. Zhemela**   *National University of Pharmacy, Kharkiv ** V. N. Karazin Kharkiv National University   Summary During experimental studies have shown the impact of dental gel "Lizostom" to reduce the duration of the microvascular bleeding, increased platelet aggregation and their capacity; increase blood clot retraction. Keywords: gel "Lizostom" vascular-platelet hemostasis, lysozyme hydrochloride.